Spectral Efficiency Optimization for Full-Duplex Distributed Antenna Systems - Liu, Zhan; Feng, Suili (2020 7th International Conference on Information Science and Control Engineering (ICISCE), 2020)
This paper investigates the spectral efficiency maximization in full-duplex distributed antenna system (DAS), where full-duplex capable remote access units (RAUs) communicate with half-duplex users. We jointly optimize uplink and downlink transmit power, subject to power constraints and the quality of service (QoS) requirements of both uplink and downlink users. User-centric virtual cell is adopted, and each user can only be served by its virtual cell to reduce the computational complexity. The formulated problem is a non-convex problem. To solve it, we convert objective function and constraint to the difference of convex (D.C.) functions, then an iterative algorithm is proposed by using successive convex approximation. The numerical results demonstrate that compared with other reference algorithms, the proposed algorithm can achieve greater spectral efficiency.